(untitled) (Педагогіка вищої та середньої школи, 2009)
The given article deals with anabwis of pedagogical guidance of technical students’ training activity in the process of professional foreign language mastering. The role of pedagogical guidance in cognitive activity of students as a component of a system is considered. Effective methods of approach to the organization of teaching professional foreign language at technical higher school are analyzed. Special attention is devoted to the methods stimulating cognitive interest of students.